IMPLEMENTASI PEMBELAJARAN DARING PENDIDIKAN AGAMA ISLAM TERHADAP HASIL BELAJAR SISWA DI SMP WAHID HASYIM MALANG - Ainur Rahman; Abdul Jalil; Eko Setiawan (VICRATINA, 2021)
Online learning is one of the lessons applied at Wahid Hasyim Middle School. Schools conduct online learning because of government policies. Some schools have implemented an online learning system. Thus the researcher wants to raise a title "Implementation of Islamic Religious Education Online Learning Against Student Learning Outcomes at Wahid Hasyim Junior High School Malang". The approach used in this research is a qualitative approach of case study research. The source of the data is primary data, namely the PAI subject teacher at Wahid Hasyim Middle School. The secondary data source is the school principal Wahid Hasyim. Data collection techniques are interviews, observation, and documentation. Data analysis techniques are data condensation, and conclusions. checking the validity of the data, namely Triangulation is the source. The implementation of online learning on student learning outcomes at Wahid Hasyim Junior High School is in the online learning model used is video. The videos that will be given to students include written and practical materials and assignments. With the learning video, there is a realm in learning which consists of attitudes, knowledge and skills. This area is currently declining but is not an obstacle in learning outcomes because students have textbooks. The inhibiting factors of online learning on student learning outcomes at Wahid Hasyim Middle School are internal and external. supporting factors only contain external factors